Platelet Aggregation Activities of Vietnamese Medicinal Plants: Anti-Thrombolytic Potentials? - Phu Hung, Luong; Thi Van Anh, Nguyen; Tien Dung, Do; Thi Thom, Vu (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 36 No 2DO - 10.25073/2588-1132/vnumps.4252, 2020)
Blood coagulant, an important physiological process, underlines pathology of various diseases. Thrombosis caused by activated platelets in blood stream can lead to narrowing or blocking the blood flow, which results in stroke or ischemic conditions. The number of human deaths caused by coronary disease or stroke has been increasing rapidly over the last few years in Vietnam. Many anti-thrombosis and anti-platelet aggregation drugs have been discovered and applied in treatment. However, these drugs have many side effects such as bleeding, stomach lesion, etc. Vietnam is a tropical country with plenty of medicinal plants, from which a potential drug for anti-thrombolytic activities can be prepared. Therefore, an overview of Vietnamese medicinal plants with anti-platelet aggregation activities, such as Panax L., Canna , is highly needed for improving the quality of exploiting Vietnamese medicinal resources. Keywords Anti-thrombosis, Canna, Panax L., platelet aggregation, Vietnamese medicinal plants. References [1] P.T.M. Duc, Physiology, Vietnamese Medical Publisher, 2006 (in Vietnamese). [2] S. H. Yun, E.H. Sim, R.Y. Goh, J.I. Park, J.Y. Han, Platelet Activation: The Mechanisms and Potential Biomarkers, Biomed Res Int, 2016. https://doi.org/10.1155/2016/9060143. [3] E.K. Shin, H. Park, J.Y. Noh, K.M. Lim, J.H. Chung, Platelet Shape Changes and Cytoskeleton Dynamics as Novel Therapeutic Targets for Anti-Thrombotic Drugs, Biomol Ther (Seoul) 25 (2017) 223–230. https://doi.org/10.4062/biomolther.2016.138. [4] R. Flaumenhaft, A. Sharda, 19 - Platelet Secretion, in: A.D. Michelson (Ed.), Platelets (Fourth Edition), Academic Press, 2019, pp. 349–370. https://doi.org/10.1016/B978-0-12-813456-6.00019-9. [5] S.A. Smith, J.H. Morrissey, 21 - Interactions Between Platelets and the Coagulation System, in: A.D. Michelson (Ed.), Platelets (Fourth Edition), Academic Press, 2019, pp. 393–400. https://doi.org/10.1016/B978-0-12-813456-6.00021-7. [6] H.P. Rang, M.M. Dale, J.M. Ritter, R. Flower, G. Henderson, Rang & Dale’s Pharmacology, 7th Edition, Churchill Livingstone, 2011. [7] L. Luyen, V. Thom, L.T. Huong, D.L. Huong, N.V. Anh, Inhibitory effect on human platelet aggregation, antioxidant activity, and phytochemicals of Canna warszewiczii (A. Dietr) Nb. tanaka, Phcog Res. 12 (2020) 47. https://doi.org/10.4103/pr.pr_72_19. [8] B.G. Katzung, A.J. Trevor, Basic & Clinical Pharmacology, 13th ed., Lange, 2015. [9] T. Pham, N. Pham, T.V. Ta, K. Pham, T. Vu, L. Dinh, VKORC1 and CYP2C9*3 Polymorphisms and Their Impacts to Acenocoumarol Dosage in Vietnamese Heart Valve Replacement Patients †1, 2018. [10] J.D. McFadyen, M. Schaff, K. Peter, Current and future antiplatelet therapies: emphasis on preserving haemostasis, Nat Rev Cardiol. 15 (2018) 181–191. https://doi.org/10.1038/nrcardio.2017.206. [11] N.A. Trí, Clinical Coagulation, Vietnam Medical Publisher, 2008 (in Vietnamese). [12] C. Gachet, Antiplatelet drugs: which targets for which treatments?, Journal of Thrombosis and Haemostasis. 13 (2015) S313–S322. https://doi.org/10.1111/jth.12947. [13] V.T Thom, V.P. Thao, V.N. Trung, N.T.T. Mau, The relationship between platelet aggregation and CYP2C19*2, CYP2C19*3 genotypes with other factors in patients with unstable angina, VNU Journal of Science: Medical and Pharmaceutical Sciences 34 (2018) 74–81. [14] C. Patrono, J. Morais, C. Baigent, J.-P. Collet, D. Fitzgerald, S. Halvorsen, B. Rocca, A. Siegbahn, R.F. Storey, G. Vilahur, Antiplatelet Agents for the Treatment and Prevention of Coronary Atherothrombosis, J Am Coll Cardiol 70 (2017) 1760–1776. https://doi.org/10.1016/j.jacc.2017.08.037. [15] R. Teng, Ticagrelor: Pharmacokinetic, Pharmacodynamic and Pharmacogenetic Profile: An Update, Clin Pharmacokinet 54 (2015) 1125–1138. https://doi.org/10.1007/s40262-015-0290-2. [16] R.J. Gryka, L.F. Buckley, S.M. Anderson, Vorapaxar: The Current Role and Future Directions of a Novel Protease-Activated Receptor Antagonist for Risk Reduction in Atherosclerotic Disease, Drugs R D. 17 (2017) 65–72. https://doi.org/10.1007/s40268-016-0158-4. [17] V.D. Loi, T.T. Vung, L.T.T. Huong, Medicial Plants, VNU publisher, 2016. [18] N.V. Đạt, T.T.P. Anh, V.T. Chinh, P.K. Long, H.L.T. Anh, Panax L (Araliaceae) in Vietnam 2017, pp. 106–111 (in Vietnamese). [19] D.T, Lợi, Vietnamese medicinal plants and traditional medicine, Vietnam Medical Publisher, 2004 (in Vietnamese). [20] N.T.T. Trinh., L.T. Tam, V.T. Thom, Đ.Đ Long, D.T.L. Huong, Influence of various fractions extracted from Panax bipinnatifidus (Seem.) on the blood coagulation and platelet aggregation in vitro, Vietnam Pharmaceutical Journal 58 (2018) 06-11–11. [21] L.T.T. Hoa, N.T. Giang, D.T.L. Huong, V.T. Thom Study on the effects of saponin-enriched extracts of Panax bipinnatifidus Seem. and Panax stipuleanatus H.Tsai et K.M.Feng on anti-aggregation activities of platelet in vitro, Journal of Research in Traditional Medicine and Pharmacy 57(2018) 49-60. [22] N.Đ. Phuong, N.D. Nhu, N.D. Thuan, New medicinal plants in Vietnam - Canna warszewiczii A.Dietr, Vietnam Pharmaceutical Journal 476 (2015) 20–23 (in Vietnamese). [23] T.V.A. Nguyen, H.D.T. Ly, T.T. Vu, T.T. Nguyen, H.L. Le, Novel finding on anticoagulant activity of Canna warszewiczii extracts, Asian Journal of Pharmacognosy 2(2) (2018) 30-34.